Integrating global geochemical volcano rock composition with eruption history datasets - Oggier, Frédérique; Widiwijayanti, Christina; Costa, Fidel (Frontiers in Earth Science, 2023)
The major element composition of volcanic rocks carries important information about the source and differentiation processes affecting the magma, the physical properties that allow it to erupt, and its eruptive style. Although global rock geochemical databases exist, these are not linked to volcanic eruption history which hampers our global understanding of the relationship between magma composition and eruption dynamics. Here, we integrate two global databases, the Geochemistry of Rocks of the Oceans and Continents (GEOROC) and the Holocene volcanoes of the world of the Global Volcanism Program (VOTW-GVP). The integration is based on matching the location name, geographic position and eruption time, which is automated by a tool called DashVolcano. The tool is open-source, accessible at https://github.com/feog/DashVolcano, and gives access to the integrated datasets via an interactive dashboard. DashVolcano is based on more than 138,000 volcanic rock samples and provides the basis for the identification of global relationships between eruption styles, volcano types, and rock composition for more than 700 volcanoes and their eruptions for the last 10,000 years. The combined record of the eruptive history and its corresponding geochemical rockIntegrating global geochemical volcano rock composition that DashVolcano provides can be used for characterizing global geochemical differences between volcanoes, and should also prove useful for improved long-term hazard and risk evaluations.